Interactions between size grading and the physiological factors limiting the germination of sugar beet fruits : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Plant Science (Seed Technology) at Massey University, Palmerston North, New Zealand - Shoar, Majid Dehghan (Massey University, 1992)
The quality and quantity of the sugar produced from sugar beet is strongly dependent on optimizing plant spacing in the field. Poor germinability and, in particular, low plant establishment, has long been a problem in sugar beet production, particularly in precision drill sowing systems designed to omit thinning, which is a time consuming process with high labour costs. In addition to physical and environmental stresses accruing in the field during germination and seedling emergence, fruit size and the physiological characteristics of the fruit itself have also been considered as very important factors involved in poor plant establishment. This experiment was carried out using samples of three lots of a diploid monogerm cultivar (9597) which was released in Iran in 1985 and continues to be produced by the Sugar Beet Seed Institute of Iran (S.B.S.I.). According to the germination capacity of ungraded fruit, these lots were categorized as medium (LOT A), low (LOT B) and high (LOT C) quality lots and were selected to determine whether there was any similarity in the relationships between fruit size and quality within different lots. Despite there being a linear and highly significant correlation (r= 0.96***) between fruit diameter and germination as well as fruit diameter and plant establishment in the low quality lot, the nature of these relationships in the medium and high quality lots were different in that the large fruits showed equal or lower germination and planting value than the medium fruit sizes. No apparent relationship was found between fruit thickness and germination performance of the seed lots. Although there was no significant correlation between the laboratory standard germination result for both thickness and diameter graded fruits and plant establishment of the high quality lot, highly significant correlations were found between the laboratory germination and plant establishment of the size grades of the medium and poor quality lots (r= 0.91 and 0.99 for Lots A and B, respectively). This appeared to be a function of the variation in germination performance of the size grades and suggests that, although in poor and medium quality lots the germination percentage of the fruit can sometimes be used as an index of field performance, in high quality lots more emphasis should be placed on the vigour of the seed. The results obtained via size grading of the seed lots used in this study illustrated that 60% of harvested fruits of each lot were either too small or too big to be used for the precision drill sowing system. Further, it was also found that 24% of the fruits within the suitable size grades were either seedless (seeds aborted) or contained under developed seed. X-radiography of the size graded fruits of the medium quality lot (A) illustrated that, despite the fact that immaturity was mostly associated with the smallest fruits (where 64% of the fruits were immature), about 18% of the larger fruits (4-5mm diameter) also contained immature seed. An important point to note is that 11-12 % of fruits with fully mature seed in the small and larger size grades did not germinate when incubated in optimal conditions. In contrast, only 3% of the fruits of the medium size grade did not germinate. This indicates that other germination limiting factors besides immaturity are involved and that they may vary between size grades. Because of its role in impeding radicle emergence and/or oxygen entrance into the seed cavity, cap tightness is known to be an important germination limiting factor in sugar beet. Thus the tighter the seed cap, the lower the germination of the fruit. Direct measurement of the force required for cap movement indicated that cap removal in larger fruits required a greater force than in small fruits. These results were in a similar range to those found by Morris et al. (1985) via indirect estimates, suggesting that enzymatic action on cap loosening is unlikely to play an important role in cap removal and therefore the direct method used in this study may be useful for selection of progenies with a reasonably loose seed cap. Chemical inhibitory substances in the fruit pericarp have been shown to be the other important factors inhibiting germination of the seed. As they are water soluble, germination improvement may be obtained following prewashing of the fruits. Despite significant germination improvement on pleated paper after prewashing of the fruits of the high quality lot (C), no improvement was obtained via prewashing the size grades of the medium and poor quality lots. However, a significant germination improvement was achieved when prewashed fruits of the medium seed quality lot were incubated on a wetter substrate in Petri-dishes. It was found that the pericarp base is the main entry route of oxygen to the seed cavity and removal of this resulted in a 29% increase in germination percentage of the thick fruit of lot A when incubated in Petri dishes. This is attributed to shortening the path for oxygen transfer to the seed cavity. However, a similar improvement in germination was also obtained via prewashing the intact fruit and a synergistic improvement in germination (45% increase) was found as a result of prewashing plus pericarp base removal. This could be explained on the basis of increased oxygen uptake into the embryo via the removal of both chemical and physical barriers to oxygen entry to the seed cavity, but requires confirmation by further research.
Keywords: Sugar beet; Yield; Growth